Efficacy and safety of PD-1 and PD-L1 inhibitors combined with chemotherapy in randomized clinical trials among triple-negative breast cancer - Qi, Yihang; Zhang, Wenxiang; Jiang, Ray; Xu, Olivia; Kong, Xiangyi; Zhang, Lin; Fang, Yi; Wang, Jingping; Wang, Jing (Frontiers in Pharmacology, 2022)
Background: The combination of immune checkpoint inhibitors (ICI) and chemotherapy (CT) is a new strategy to explore cancer treatment in recent years, and it is also practiced in triple-negative breast cancer (TNBC). However, several published randomized controlled trials (RCTs) reported heterogeneous results. We conducted this meta-analysis to yield insights into the efficacy and safety of the combination of ICI and CT for TNBC patients in both the adjuvant and neoadjuvant settings. Method: PUBMED, EMBASE, Cochrane and www.clinicaltrials.gov databases were searched to determine eligible studies from database inception to May 20, 2022. Published RCTs on PD-1/PD-L1 ICIs combined with CT for TNBC patients were included. Result: Six double-blind RCTs comprising 4,081 TNBC breast cancer patients treated with PD-1/PD-L1 ICIs plus CT or placebo plus CT were included in this meta-analysis. The combination strategy benefited a better pathologic complete response (pCR) by 29% (RR = 1.29; 95% CI: 1.17–1.41; I2=0%) and a better progression-free survival (PFS) (HR = 0.82; 95% CI: 0.74–0.90; I2=0%) in the neoadjuvant and the adjuvant setting respectively, especially in PD-L1-positive population (HR = 0.71; 95% CI: 0.62–0.81; I2= 13%). The safety profiles were generally tolerable in both settings but the combination treatment will increase the risk of severe adverse events in the adjuvant setting (RR=1.33; 95% CI 1.08–1.62, I2= 0%). Additionally, the combination will increase the risk of any-grade hypothyroidism, hyperthyroidism, pneumonia, rash in the adjuvant setting, and the risk of any-grade hypothyroidism, hyperthyroidism, infusion-related reactions, and severe cutaneous reactions in the neoadjuvant setting. Conclusion: This meta-analysis demonstrated a significant pCR benefit and confirms the PFS benefit with PD-1/PD-L1 ICIs plus CT in TNBC patients with tolerable safety events in both neoadjuvant and adjuvant settings.